The Mediating Role of Distributive Justice, Procedural Justice, and Organizational Citizen Behavior in the Influence of Strategic Performance Measurement System on Employee Performance in the Indonesian Ministry of Finance - Yeney Widya Prihatiningtias; Sofyan Wijaya Julianto (Universitas Hayam Wuruk Perbanas, 2019)
This study aims to examine the effect of the Strategic Performance Measurement System (SPMS) on the employees’ performance through distributive justice, procedural justice, and Organizational Citizen Behavior (OCB) as the mediating variables. The respondents are the staffs and junior supervisors at the General Directorate of Treasury (GDT) of the Ministry of Finance, one of the agencies initiating the implementation of SPMS in the Indonesian public sector institution. Two hundred forty-nine data were collected using a survey method. Data analysis was performed using the structural equation model. The results show that SPMS directly affect the employees’ performance and significantly has a positive effect on distributive justice and procedural justice. Distributive justice has a positive impact on procedural justice. Procedural justice itself has a positive impact on OCB. Furthermore, OCB has a positive impact on employee performance. In addition, the effect of SPMS on the employees’ performance is mediated by distributive justice, procedural justice, and OCB. Besides that, the relationship can also be mediated only by procedural justice and OCB. Both alternatives show a complementary partial mediation relationship. This implies that the remuneration rubric, as the reflection of SPMS, needs to be matched with the individual and job characteristics, supported by the senior supervisors as the policy makers.